2014
DOI: 10.1007/s13300-014-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonist Treatment Patterns Among Type 2 Diabetes Patients in Six European Countries

Abstract: IntroductionThe objective of this study was to evaluate real-world treatment patterns of type 2 diabetes (T2D) patients initiating glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in Germany (GE), the United Kingdom (UK), France (FR), the Netherlands (NE), Belgium (BE), and Sweden (SE).MethodsAdult T2D patients initiating exenatide twice daily (exBID), liraglutide once daily (LIRA) or exenatide once weekly (exQW) were identified using the IMS LifeLink™ (IMS Health, Danbury, CT, USA): Electronic Medical Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 6 publications
4
47
0
Order By: Relevance
“…Liraglutide prescriptions were categorized as the following: all doses (any exposure to all available prescribed doses [0.6 mg, 1.2 mg, 1.8 mg per day] during the study period); 1.2 mg category, average daily dose (ADD) 0.6–1.5 mg; and liraglutide 1.8 mg category, ADD >1.5–2.1 mg [12]. ADD was calculated as the sum of the prescribed number of units (pens) multiplied by the total dosage in each unit (mg), divided by the sum of the days covered by the prescriptions.…”
Section: Methodsmentioning
confidence: 99%
“…Liraglutide prescriptions were categorized as the following: all doses (any exposure to all available prescribed doses [0.6 mg, 1.2 mg, 1.8 mg per day] during the study period); 1.2 mg category, average daily dose (ADD) 0.6–1.5 mg; and liraglutide 1.8 mg category, ADD >1.5–2.1 mg [12]. ADD was calculated as the sum of the prescribed number of units (pens) multiplied by the total dosage in each unit (mg), divided by the sum of the days covered by the prescriptions.…”
Section: Methodsmentioning
confidence: 99%
“…A total of three once‐daily GLP‐1 receptor agonists are currently available to patients: exenatide 10 µg twice daily (approved by the European Medicines Agency in 2006); liraglutide 1.2 or 1.8 mg (approved in 2009); and lixisenatide 20 µg (approved in 2013). In the UK in 2013, an analysis of the prescription records of 30 436 patients receiving liraglutide found that the mean daily dose of liraglutide was 1.49 mg, reflecting an almost equal split between the 1.2 and 1.8 mg doses . However, since collection of these data, restrictions on the use of liraglutide 1.8 mg in the UK have been removed and the proportion of patients receiving liraglutide 1.8 mg is likely to increase in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK in 2013, an analysis of the prescription records of 30 436 patients receiving liraglutide found that the mean daily dose of liraglutide was 1.49 mg, reflecting an almost equal split between the 1.2 and 1.8 mg doses. 13 However, since collection of these data, restrictions on the use of liraglutide 1.8 mg in the UK have been removed and the proportion of patients receiving liraglutide 1.8 mg is likely to increase in the future.…”
mentioning
confidence: 99%
“…Some GLAs have a low side effect profile and subsequently high rates of patient adherence to therapy, most notably DPP-4 inhibitors (33), while others do not (e.g., TZDs, SUs, GLP-1 RAs, insulin). Side effects may also partly explain why patients have higher rates of drug discontinuation in "real-world" observational trials compared with clinical trials (46). Individual patient beliefs, preferences, and specific lifestyle circumstances (for example, fear of hypoglycemia, fear of injection, high-risk occupation [drivers], tolerability of gastrointestinal side effects, etc.)…”
Section: Side Effects and Patient Adherencementioning
confidence: 99%